Influence of CO2 injection timing on enhanced coalbed methane recovery using thermo-hydro-mechanical coupled model - Hexiang Xu; Cheng Zhai; Jizhao Xu; Yong Sun; Ting Liu; Yangfeng Zheng; Hongyang Xu; Ting Huang (Case Studies in Thermal Engineering, 2025)
Delayed CO2 injection can prevent premature CO2 breakthrough to production wells during CO2 enhanced coalbed methane (CO2-ECBM) recovery. Currently, the influence of CO2 injection timing on CO2-ECBM recovery is unclear. In this paper, the thermo-hydro-mechanical (THM) coupled model was established to investigate the CO2-ECBM recovery with different injection timings. The porosity evolution characteristics and the optimal injection timing were determined. The results show that high-pressure CO2 injection elevates reservoir pressure and enhances CH4 production. As injection time increases, reservoir temperature rises, and permeability declines. Delayed CO2 injection can avoid inefficient injection stage and maintain a higher injection rate. Injection timing showed linear correlations with CH4 production, CO2 storage volume, and breakthrough time, and an S-shaped trend with final CH4 concentration. CO2 injection shortens the pore pressure-dominated control stage of porosity and amplifies the influence of gas ad/desorption-induced strain. Temperature changes have a minor effect on porosity, but high initial temperature can reduce gas adsorption, significantly affecting porosity. Finally, the optimal injection time was determined as 1000 d. The results are beneficial for improving the CH4 recovery and realizing the efficient CO2 storage.